Literature Study Analysis of Daily Inpatient Census Implementation for Reporting of Hospital Inpatient Service Indicators - Dytia Utami; Nopita Cahyaningrum; Syahril Anuar Bin Idris (Proceedings of the International Conference on Nursing and Health Sciences, 2022)
The implementation of the daily census of hospitalization must be carried out according to procedures properly and correctly so that the data used can be utilized optimally by the hospital. The utilization of this reporting data relates to the mechanism of service procedure flow for the internal and external interests of the hospital. The general objective in this research is to know the implementation of daily inpatient census for reporting of inpatient service indicators incorrect. Method: This research is a literature study with research instruments using google chrome and google scholar. Sample of 6 journals related to the daily census of hospitalizations. The results showed that 6 out of 6 daily census journals of hospitalizations were not in accordance with the procedures both in terms of officers and the implementation of the daily census of hospitalizations. Results: The data sources used in the creation of the daily census of hospitalizations are inpatient register books and medical record documents. The utilization of daily census data of hospitalizations 2 out of 6 journals has utilized daily census data to the maximum because daily census data is used as decision making by hospital management. Conclusions: The advice from this study is that hospitals should create or update fixed procedures and instructions covering all activities of the mechanism for implementing the Daily Census of Hospitalization, and hospitals should hold training or socialization of writing/filling technical instructions and fixed procedures on the Daily Census of Hospitalization.